A suite of broadband physics‐based ground motion simulations for the Istanbul region. (7th January 2023) - Zhang, Wenyang; Crempien, Jorge G.F.; Kurtulus, Asli; Chen, Peng‐Yu; Arduino, Pedro; Taciroglu, Ertugrul
Abstract: Physics‐based earthquake ground motion simulations (GMS) have acquired significant growth over the last two decades, mainly due to the explosive developments of high‐performance computing techniques and resources. These techniques benefit high/medium seismicity regions such as the city of Istanbul, which presents insufficient historical ground motion data to properly estimate seismic hazard and risk. We circumvent this reality with the aid of the Texas Advanced Computing Center (TACC) facilities to perform a suite of 57 high‐fidelity broadband (8–12 Hz) large‐scale physics‐based GMS for a region in Istanbul, Turkey. This paper focuses on the details of simulated GMS: (i) validation of the GMS approach against recorded ground motions produced by the 2019 M w 5.7 $M_{w}\nobreakspace 5.7$ Silivri earthquake; (ii) characteristics of 57 different source models, which aim to consider the uncertainties of many fault rupture features, including the length and width, dip, strike, and rake angles of considered fault planes, as well as hypocenter locations and earthquake magnitudes ranging between M w $M_{w}$ 6.5 and 7.2; (iii) high‐resolution topography and bathymetry and seismic data that are incorporated into all GMS; (iv) simulation results, such as PGAs and PGVs versus V s 30 $V_{s30}$ and distances to fault ruptures ( R rup $R_{\text{rup}}$ ), of 2912 surface stations for all 57 GMS. More importantly, this research provides a massive database of displacement, velocity and acceleration time histories in all three directions over more than 20, 000 stations at both surface and bedrock levels. Such site‐specific high‐density and ‐frequency simulated ground motions can notably contribute to the seismic risk assessment of this region and many other applications.